2002
DOI: 10.1034/j.1600-0501.2002.130610.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin, deoxypyridinoline and interleukin‐1β in peri‐implant crevicular fluid of patients with peri‐implantitis

Abstract: The aim of the present study was to analyze the levels of osteocalcin, deoxypyridinoline (Dpd) and interleukin-1beta as markers of bone metabolism in peri-implant crevicular fluid (PICF) from peri-implantitis patients. PICF was sampled from a total of 34 endosseous titanium implants from 16 patients; nine females (mean age 52.8, range 40-62 years) and seven males (mean age 56.0, range 36-66 years). The implants had been in place for a period of 9-112 months (mean; 35.8 months) since the loading. These sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(149 citation statements)
references
References 38 publications
10
134
3
2
Order By: Relevance
“…However, the presence of a specific SNP does not necessarily translate into higher levels of IL-1β in PICF (Lachmann et al 2007;Jansson et al 2005;Melo et al 2012). Although there is good evidence of the involvement of IL-1β as a crucial mediator of the host inflammatory response in peri-implant tissues (Murata et al 2002;Salvi et al 2010;Ataoglu et al 2002), this needs to be complemented with further interventional studies, whereby IL-1β inhibitors are part of the treatment. Moreover, other members of the IL-1 family, such as IL-18, which may display differential regulation from IL-1β, should also be considered in PICF (Hamedi et al 2009;Bostanci et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of a specific SNP does not necessarily translate into higher levels of IL-1β in PICF (Lachmann et al 2007;Jansson et al 2005;Melo et al 2012). Although there is good evidence of the involvement of IL-1β as a crucial mediator of the host inflammatory response in peri-implant tissues (Murata et al 2002;Salvi et al 2010;Ataoglu et al 2002), this needs to be complemented with further interventional studies, whereby IL-1β inhibitors are part of the treatment. Moreover, other members of the IL-1 family, such as IL-18, which may display differential regulation from IL-1β, should also be considered in PICF (Hamedi et al 2009;Bostanci et al 2009).…”
mentioning
confidence: 99%
“…A few studies looking into other markers of bone metabolism, such as osteocalcin, reported that these are higher in PICF from peri-implant mucositis compared to healthy sites, whereas no differences were observed between periimplatitis and either mucositis or health. Hence, elevated levels of osteocalcin in PICF may 18 reflect increased local bone turnover around implants, rather than severe bone resoprtion (Murata et al 2002).…”
mentioning
confidence: 99%
“…TNF-α stimulates bone resorption and fibroblasts to produce collagenase [29,30]. The detected levels of TNF-α in this study were very low for all four groups.…”
Section: Healthy Teeth and Healthy Implantsmentioning
confidence: 91%
“…Biochemical markers in peri-implant crevicular fluid may indicate peri-implantitis in early stage, allowing efficient intervention before substantial amounts of bone are lost. Some biochemical markers have been suggested to detect peri-implant disease (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%